Faktor-Faktor Yang Memengaruhi Keputusan Pembelian Produk Merchandise K-Pop - Nadiah Salma Salsabila; Muhamad Yunanto (Journal of Economic and Business Advancement, 2026)
This empirical study examines the determinants of purchase decisions for K-Pop merchandise within the Group Order Senja community using a quantitative descriptive approach and Structural Equation Modeling–Partial Least Squares (SEM-PLS). The sample consists of 180 respondents selected through purposive sampling from a population of 479 active K-Pop fans who have purchased merchandise collectively. The findings demonstrate that consumer trust, price perception, and social value significantly influence purchase decisions, while social influence acts as a partial mediating variable. Consumer trust exhibits the strongest direct effect on purchase decisions, highlighting the importance of credibility and perceived transaction security in collective purchasing systems. Social value significantly shapes social influence, reinforcing social dynamics within fandom communities. Interestingly, social influence shows a significant negative relationship with purchase decisions, suggesting the presence of psychological resistance or self-control mechanisms under social pressure.